A virtual reality electrocardiography teaching tool - O'SULLIVAN, CAROL ANN (My University, 2004)
We present a novel approach to producing a tool for use in the teaching of electrocardiography. A volumetric model is attained by outputting slice information to image files, which are then used to texture polygons in the reconstruction of the volume. A time-stepping algorithm is used to synchronise the playback of the electrical depolarisation and repolarisation cycles of the heart on both the 3D cardiac model and 2D ECG graph. The tool is currently being integrated into undergraduate physiology modules.
PUBLISHED
Keywords: ECG; virtual reality; cardiac modelling